Workshop Penguatan Strategi Pembelajaran Daring Fisika Pasca Pandemi COVID-19 - Huraiza Mahmudah (Postgraduate Program, University of Mataram, 2024)
The COVID-19 pandemic has accelerated the transformation of learning from face-to-face instruction to online learning. This shift requires teachers to possess competencies in designing technology-based learning strategies to ensure effective learning processes. However, in practice, many teachers still face challenges in utilizing digital learning media, developing appropriate online learning strategies, and maintaining students’ understanding of physics concepts. This community service activity aims to enhance teachers’ competencies in designing and implementing effective online physics learning strategies through a workshop program. The implementation method consisted of several stages, including preparation, workshop implementation, practice in developing online learning materials, and activity evaluation. The results of the activity indicate that the workshop improved teachers’ understanding and skills in utilizing various digital learning media such as video conferencing platforms, interactive learning applications, and visual media for explaining physics concepts. In addition, participants demonstrated improved abilities in designing more interactive and contextual learning activities. Therefore, this workshop provides a positive contribution to strengthening the capacity of physics teachers in addressing the challenges of digital learning in the post-pandemic era.